Reverse engineering using a knowledge-based approach. (1st January 2014) - Durupt, Alexandre; Remy, Sébastien; Ducellier, Guillaume; Pouille, Philippe
This paper focuses on Reverse Engineering (RE) domain in mechanical design. RE is an activity which consists of creating a Computer-Aided Design (CAD) model from a 3D point cloud. The CAD models obtained using modern software applications are generally 'frozen' (i.e. a set of free form surfaces or a set of geometrical features in a manifold static model). Redesigning activities of these models are thus impossible. This paper proposes Knowledge-Based Reverse Engineering (KBRE), an approach which combines knowledge-based engineering with classical approaches in RE. The combination allows us to obtain a dynamic model (i.e. a set of manufacturing and design features with constraints, parameters, rules and relationships). A redesigning activity is then possible from this type of model.